Analysis of One Data Indonesia Portal User Satisfaction Using the Pieces Framework - Mulyana, Ade; Rahmawati, Rima (Jurnal Ilmiah Manajemen Kesatuan, 2024)
One data Indonesia is a platform created by the Ministry of National Development Planning or the National Development Planning Agency (PPN/BAPPENAS) to facilitate access to information for all levels of society regarding development in Indonesia. The One Data Indonesia Portal contains data and information from various government agencies, non-governmental organizations and other sources. Through the One Data Indonesia Portal, users can search for data and information related to topics such as the economy, education, health, social and environment. User satisfaction is a person's emotional feelings of pleasure or disappointment that occur when the performance (outcome) of a product is compared to the expected result (or results). The number of website users, the researcher wants to know the level of user satisfaction of One Data Indonesia Portal from the user's point of view by paying attention to user satisfaction indicators. The quantitative analysis used in the research is presented on the Satu Data Indonesia website ( www.data.go.id ), the research findings are presented as accurate numerical data. the results of the research are in the form of satisfaction level values and validity and reliability tests. The conclusion from the analysis of user satisfaction on the Indonesian one-data website using the PIECES method was carried out on 100 Indonesian one-data website user respondents whose characteristics were obtained based on the age, gender and occupation of the respondents using the PIECES domain. Keywords: User Satisfaction, Quantitative Analysis, PIECES Method